How do epiphytic and surrounding seawater bacterial communities shift with the development of the Saccharina japonica farmed in the Northern China? - Cai, Ling; Gao, Xin; Saha, Mahasweta; Han, Yixiao; Chang, Lirong; Xiao, Luyang; Wang, Gaoge (Frontiers in Marine Science, 2023)
Epibacteria of seaweeds play an important role for the development of hosts and are influenced by the planktonic surrounding seawater bacteria. However, to date, the knowledges related to both epiphytic and surrounding seawater bacterial communities associated with northern farmed Saccharina japonica are very limited. In this study, using 16S rRNA gene amplicon sequencing, the shifts of epiphytic and surrounding seawater bacterial communities of the northern farmed S. japonica from mature sporophytes, sporelings (3 time points) to juvenile sporophytes (2 time points) were investigated. The dominant genera of epibacterial communities were Alcanivorax (mature sporophytes and 4-week-old sporelings), Bacillus (7-week-old sporelings and 9-week-old sporelings), Halomonas (4-week-old juvenile sporophytes) and Cobetia (9-week-old juvenile sporophytes). Meanwhile, the Chao1 indexes and beta diversity of epibacterial communities were significantly different with the development of S. japonica (p < 0.05). Furthermore, Alcanivorax, Bacillus and Halomonas were both dominant and core genera, indicating that these taxa may be beneficial to the development of S. japonica. The alpha diversity indexes of both epiphytic and surrounding seawater bacterial communities were significantly different for 9-week-old juvenile sporophytes. Therefore, the epibacterial communities were influenced by both development of S. japonica and the surrounding seawater bacterial communities. This study not only extends the understanding of the bacterial communities associated with the northern farmed S. japonica, but also help to make production management by monitoring the variations in both epiphytic and surrounding seawater bacterial communities.